2018
DOI: 10.1093/cercor/bhy091
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Age is Dimensionally Associated with Structural Brain Network Abnormalities Across Development

Abstract: Prematurity is associated with diverse developmental abnormalities, yet few studies relate cognitive and neurostructural deficits to a dimensional measure of prematurity. Leveraging a large sample of children, adolescents, and young adults (age 8-22 years) studied as part of the Philadelphia Neurodevelopmental Cohort, we examined how variation in gestational age impacted cognition and brain structure later in development. Participants included 72 preterm youth born before 37 weeks' gestation and 206 youth who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 95 publications
(144 reference statements)
3
24
0
Order By: Relevance
“…We used NNMF (see the Supplement for more information) to identify SCNs in the neonatal preterm brain in which regional brain volumes consistently covary across individuals ( N = 384). NNMF is an unsupervised multivariate dimension reduction technique that is particularly suited for investigating brain structural covariance ( 26 , 51 ). In contrast to seed-based approaches ( 52 ), NNMF derives networks in a data-driven manner.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used NNMF (see the Supplement for more information) to identify SCNs in the neonatal preterm brain in which regional brain volumes consistently covary across individuals ( N = 384). NNMF is an unsupervised multivariate dimension reduction technique that is particularly suited for investigating brain structural covariance ( 26 , 51 ). In contrast to seed-based approaches ( 52 ), NNMF derives networks in a data-driven manner.…”
Section: Methodsmentioning
confidence: 99%
“…Altered structural covariance has been reported in preterm-born adolescents ( 24 ) and young adults ( 25 ). Notably, the association between low gestational age at birth (GA) and executive deficits was shown to be mediated by altered structural covariance in orbitofrontal, temporal, parietal, and subcortical regions in a large sample of adolescents ( 26 ). However, it is unclear to what extent SCNs emerging in the neonatal period might predict developmental outcomes after preterm birth.…”
mentioning
confidence: 99%
“…This can be achieved with NMF, which is an unsupervised algorithm based on decomposition by parts and a model selection mechanism. NMF has been used to iteratively select the most robust biomarkers from thousands of genes (Zhong et al, 2018;Zeng et al, 2019;Motzer et al, 2020) and to find structural covariance patterns in neuroimaging content (Nassar et al, 2019;Patel et al, 2020). In our application of NMF to radiomic features, the parts were the components of a reduced representation of the original hidden features, which may enable the recovery of biologically similar phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have concluded that early preterm birth is associated with a high level of attention-deficit/hyperactivity disorder (ADHD) symptoms in preschool children [ 17 ]. Gestational age is dimensionally related to structural brain network abnormalities across development [ 18 ]. In addition, lower birth weight may cause lagging brain development [ 19 ].…”
Section: Discussionmentioning
confidence: 99%